(untitled) - Ricardo, David (New York, 1971)
There can be no rise in the value of labor without a fall of profits. If the corn is to be divided between the farmer and the laborer, the larger the proportion that is given to the latter the less will remain for the former -from "On Value" Friend to, colleague of, and influence on the likes of James Mill, Jeremy Bentham, and Thomas Malthus, revolutionary British writer DAVID RICARDO (1772-1823) was one of the foundational thinkers of classical economics, developing theories of rent, wages, profits, value, and labor that continue to dramatically impact economic philosophy today. Principles of Political Economy and Taxation, first published in 1817, is his major work. Here, he introduces the concept of comparative advantage, explores the impact of taxes, examines the effects of accumulation of profits and interest, discusses trade, currency, and banks, and much more. ALSO FROM COSIMO: Ricardo's Classics of Economics: The High Price of Bullion and An Essay on Profits
Keywords: Economics,Kinh tế